A Survey of Nucleotide Cyclases in Actinobacteria: Unique Domain Organization and Expansion of the Class III Cyclase Family in Mycobacterium tuberculosis. Issue 1 (2004) - Shenoy, Avinash R.; Sivakumar, K.; Krupa, A.; Srinivasan, N.; Visweswariah, Sandhya S.
Abstract : Cyclic nucleotides are well-known second messengers involved in the regulation of important metabolic pathways or virulence factors. There are six different classes of nucleotide cyclases that can accomplish the task of generating cAMP, and four of these are restricted to the prokaryotes. The role of cAMP has been implicated in the virulence and regulation of secondary metabolites in the phylum Actinobacteria, which contains important pathogens, such as Mycobacterium tuberculosis, M. leprae, M. bovis and Corynebacterium, and industrial organisms from the genus Streptomyces . We have analysed the actinobacterial genome sequences found in current databases for the presence of different classes of nucleotide cyclases, and find that only class III cyclases are present in these organisms. Importantly, prominent members such as M. tuberculosis and M. leprae have 17 and 4 class III cyclases, respectively, encoded in their genomes, some of which display interesting domain fusions seen for the first time. In addition, a pseudogene corresponding to a cyclase from M. avium has been identified as the only cyclase pseudogene in M. tuberculosis and M. bovis . The Corynebacterium and Streptomyces genomes encode only a single adenylyl cyclase each, both of which have corresponding orthologues in M. tuberculosis . A clustering of the cyclase domains in Actinobacteria reveals the presence of typical eukaryote-like, fungi-like and other bacteria-like class III cyclase sequences within this phylum, suggesting that these proteins may have significant roles to play in this important group of organisms.